Comparative Analysis of Plant Diversity with Reference to Chamundi Hills in Mysore District of Karnataka State, India - Swamy, M. M.; Veerabhadra Swamy, A. L.; Anuradha, R. P. (Indian Forester, 2017)
The forest cover in Chamundi hills ranges from dry scrub vegetation to dry deciduous forest type. The study was undertaken by foot survey method. There are 483 species of flowering plants, spread under 94 families. Among these, 423 species of plants belong to dicotyledonous group and 60 species of plants come under monocotyledonous group. Asteraceae, Fabaceae, Euphorbiaceae, Rubiaceae and Poaceae families with high number of plant species. There are about 24 common shrubs and trees, 11 rare and important plants and 65 medicinally important plants were recorded during the field visit and few plant species were preserved in the herbarium.